2018
DOI: 10.1016/j.celrep.2018.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Vesicle Fusion Is Differentially Regulated at Cholinergic and GABAergic Synapses

Abstract: The locomotion of C. elegans is balanced by excitatory and inhibitory neurotransmitter release at neuromuscular junctions. However, the molecular mechanisms that maintain the balance of synaptic transmission remain enigmatic. Here, we investigated the function of voltage-gated Ca channels in triggering spontaneous release at cholinergic and GABAergic synapses. Recordings of the miniature excitatory/inhibitory postsynaptic currents (mEPSCs and mIPSCs, respectively) showed that UNC-2/CaV2 and EGL-19/CaV1 channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
49
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 43 publications
11
49
1
Order By: Relevance
“…We next examined the functional roles of the C2A/C2A homodimerization and C2A/RIM heterodimerization in tonic neurotransmitter release by measuring miniature excitatory/inhibitory postsynaptic currents (mEPSCs/mIPSCs) at the neuromuscular junction. Both the mEPSCs and the mIPSCs were recorded in the presence of 0mM and 1mM Ca 2+ , as we have previously found that the mIPSCs are nearly arrested in 0mM Ca 2+ but are normal 1mM Ca 2+ in some mutants (Liu et al, 2018), suggesting that different Ca 2+ concentrations should be tested to provide an accurate and thorough evaluation of tonic release. Our results showed that the mEPSCs and mIPSCs were completely abolished in the unc-13(s69) null mutant, and were fully restored by neuronal expression of full-length UNC-13L ( Figure 2).…”
Section: Disrupting C2a/rim Heterodimerization Reduces Mepscs/mipscs mentioning
confidence: 99%
See 1 more Smart Citation
“…We next examined the functional roles of the C2A/C2A homodimerization and C2A/RIM heterodimerization in tonic neurotransmitter release by measuring miniature excitatory/inhibitory postsynaptic currents (mEPSCs/mIPSCs) at the neuromuscular junction. Both the mEPSCs and the mIPSCs were recorded in the presence of 0mM and 1mM Ca 2+ , as we have previously found that the mIPSCs are nearly arrested in 0mM Ca 2+ but are normal 1mM Ca 2+ in some mutants (Liu et al, 2018), suggesting that different Ca 2+ concentrations should be tested to provide an accurate and thorough evaluation of tonic release. Our results showed that the mEPSCs and mIPSCs were completely abolished in the unc-13(s69) null mutant, and were fully restored by neuronal expression of full-length UNC-13L ( Figure 2).…”
Section: Disrupting C2a/rim Heterodimerization Reduces Mepscs/mipscs mentioning
confidence: 99%
“…Thus, the UNC-13L C2A domain is important for tonic release of both ACh and GABA; however, the requirement for C2A in GABA release can be bypassed by the presence of extracellular calcium, presumably due to increased release probability. The differential impact of deleting C2A on ACh and GABA release in 1mM Ca 2+ could reflect differences in release probability at these two types of synapses (Liu et al, 2018). In fact, SV release from inhibitory synapses displays a higher release probability than excitatory synapses in the mammalian central nervous system (Zhou et al, 2013b;Zhou et al, 2013c).…”
Section: Disrupting C2a/rim Heterodimerization Reduces Mepscs/mipscs mentioning
confidence: 99%
“…Over 15 synaptotagmin isoforms have been identified in mammals, several of which have been shown to be important for synaptic vesicle (SV) exocytosis (Brose et al, 1992;Xu et al, 2007;Weber et al, 2014). Synaptotagmin-1 (Syt1), one of the most important members of the family, has been demonstrated to act as the major Ca 2ϩ sensor of neurotransmitter release at many types of synapses (Geppert et al, 1994;Yoshihara and Littleton, 2002;Lee et al, 2013;. Each C2 domain of Syt1 contains five Ca 2ϩ -binding residues (aspartates; Nishiki and Augustine, 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…An unc-2 gain-of-function mutation results in E/I imbalance Presynaptic Ca 2+ influx through CaV2 channels is tightly coupled to neurotransmitter release. In accordance, unc-2 loss-of-function mutants are resistant to the acetylcholinesterase inhibitor aldicarb (Miller et al, 1996), and have a reduction in spontaneous EPSC frequency (Richmond et al, 2001;Tong et al, 2015;Liu et al, 2018). The unc-2(gf) mutation increases Ca 2+ influx, which would lead to an increase in neurotransmitter release probability.…”
Section: Discussionmentioning
confidence: 91%